(untitled) (The Review of Diabetic Studies, 2024)
Asthma is a chronic inflammatory airway disease often presenting more severely in adults compared to children. This paper analyzes adult-onset asthma through a case study showcasing atypical features, such as workplace triggers and silent hypoxemia, alongside comorbidities like allergic rhinitis. It discusses pathophysiological mechanisms and clinical manifestations linked to chronic airway inflammation. Current guidelines recommend inhaled corticosteroids and ICS formoterol regimens, with potential use of biologic therapies for Type 2 inflammation. Respiratory therapists play a crucial role in spirometry and exacerbation management, while advanced practice nurses focus on ongoing assessment and patient education. The analysis highlights discrepancies between textbook descriptions and clinical realities, emphasizing the need for integrated, patient-centered care to prevent long-term airway damage and improve symptom control in adults with asthma.